Design and Analysis of RFID Microwave Antennas - Dalia, Richa (My University, 2016)
Living in a scenario where automation greatly replaces manual work, we are lucky to be bestowed with RFID technology. It is continuously gaining wide popularity because of the various advantages like high speed, minimized error rates, reduced shrinkage. Various application areas supported by RFID technology include supported automated manufacturing, tracking, management of supply chain, healthcare etc. But considering the other side also, the technology has only found limited implementation because of the lack of robustness and reliability, availability of cheaper alternatives like barcode. Common standards and interoperability also lacks. Keeping in mind the drawbacks suffered by this technology, microstrip antennas serve as a solution to an extent. As these antennas are low profile, light, compatible with integrated circuits and hence cost efficient. But because these antennas have narrow bandwidth and low gain, therefore methods need to be devised to improve these factors. Using slotting technique, CPW feed and cutting triangular notches at the edges can prove beneficial. The major concern regarding RFID antennas is their size. They should be compact and simple in design so that they can be easily mounted on chip of the object to be tracked. In this thesis RFID antennas for microwave range are introduced. The central frequencies for these antennas are 2.4 GHz and 5.8 GHz. The antenna design for 2.4 GHz consists of bevelled rectangular patch with rectangular slots and the antenna design for 5.8 GHz contains Jerusalem cross shaped patch with rectangular slots. Both the antennas are CPW fed and support wide bandwidth. The antenna operating at 2.4 GHz can be used for asset tracking, temperature management, vehicle access control, shipping container management, personnel tracking health care, manufacturing, building access control. The antenna can also be used for bluetooth, zigbee, WLAN which all work at 2.4 GHz. The antenna designed for 5.8 GHz can be used for long range access control for vehicles, vehicle identification, supply chain, automated toll collection. RFID antennas at 5.8 GHz has various advantages like more available bandwidth, resistant to conductive object degradation, smaller tag footprint, allows integration of multiple antennas onto compact RF tag and hence giving new signalling schemes. This band supports better signal propagation; manage large capacity real-time location systems efficiently.
Keywords: RFID; Anetnna; bandwidth